Harmonizing Ecotourism In Indonesia: Balancing The Green Economy, Cultural Heritage, And Biodiversity - Eko Baroto Waluyo; Bambang Guritno (International Conference On Digital Advanced Tourism Management And Technology, 2023)
The literature review is intended to explore the dynamics of sustainable ecotourism in Indonesia by considering the balance between the green economy, socio-cultural dimensions and biodiversity conservation. We examine how ecotourism functions as a catalyst for sustainable economic growth while assessing its impact on local communities, cultural heritage, and the natural environment. This study underscores the importance of conserving and maintaining biodiversity in the context of ecotourism to maintain the balance of our ecosystem. Substantial analysis is carried out through an exploratory and observational approach to systematically and comprehensively evaluate various types of data sources from various sources from all over the world, including books, journals, research reports, and many other sources that are related to the field of tourism and especially ecotourism in Indonesia. It is hoped that the results can be used as a lens in evaluating the evolution, achievements and obstacles faced in sustainable ecotourism practices, including providing in-depth insight into the potential of ecotourism as a sustainable solution for economic prosperity, cultural preservation and biodiversity protection.